2015
DOI: 10.1021/acsami.5b01210
|View full text |Cite
|
Sign up to set email alerts
|

Highly Efficient Antibacterial Surface Grafted with a Triclosan-Decorated Poly(N-Hydroxyethylacrylamide) Brush

Abstract: This work presented a highly efficient antibacterial Ti-surface which was grafted with poly(N-hydroxyethylacrylamide) (PHEAA) brush and further decorated with triclosan (TCS). The modified surfaces were characterized using contact angle measurements, X-ray photoelectron spectroscopy, and attenuated total reflectance Fourier transform infrared. The antibacterial performance of the modified surfaces was evaluated using the Streptococcus mutans and Actinomyces naeslundii attachment test. The Ti surface with PHEAA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
50
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(53 citation statements)
references
References 54 publications
3
50
0
Order By: Relevance
“…7−9 For contact killing (e.g., cationic polymers, quaternary ammonium salts, or physical puncture) and antiadhesion coatings (e.g., PEG), the dead bacteria on the surface of antibacterial coatings also inhibit further antibacterial performance. 10,11 It is well known that the recurrence of implant infection is common within many years. 12,13 Recently, implant coatings with photodynamic and photothermal antibacterial properties have been reported; these present exogenous antibacterial strategies for noninvasive, efficient, and in situ treatments of implant infection.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…7−9 For contact killing (e.g., cationic polymers, quaternary ammonium salts, or physical puncture) and antiadhesion coatings (e.g., PEG), the dead bacteria on the surface of antibacterial coatings also inhibit further antibacterial performance. 10,11 It is well known that the recurrence of implant infection is common within many years. 12,13 Recently, implant coatings with photodynamic and photothermal antibacterial properties have been reported; these present exogenous antibacterial strategies for noninvasive, efficient, and in situ treatments of implant infection.…”
mentioning
confidence: 99%
“…Thus, many researchers have focused on studying the use of antibacterial coatings on the surface of implants, which can actively kill bacteria or passively prevent their attachment. Release-based antibacterial coatings can inhibit bacterial infection by releasing antibacterial agents ( e.g ., antibiotics, Ag ions, Cu ions, chlorhexidine, or antibacterial peptides); however, the potential toxicity of the antibacterial agents cannot be ignored, and the antibacterial ability of the coatings will become invalid due to their instability. For contact killing ( e.g ., cationic polymers, quaternary ammonium salts, or physical puncture) and antiadhesion coatings ( e.g ., PEG), the dead bacteria on the surface of antibacterial coatings also inhibit further antibacterial performance. , …”
mentioning
confidence: 99%
“…Triclosan, a widely used antibacterial and antifungal agent, is present in everyday household personal care and consumer products ( 11 , 12 ). Moreover, previous studies have focused on its antibacterial effect ( 14 – 16 ). To the best of our knowledge, the present study is the first to identify that triclosan induces cell death and autophagy in A375 cells.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, triclosan may have anticancer effects in melanoma cells. Previous studies have focused on its antibacterial effects ( 14 – 16 ), thus few studies have investigated its anticancer properties and its effects in melanoma have not been shown.…”
Section: Introductionmentioning
confidence: 99%
“…Triclosan (TCN) is a well-known antibacterial agent used in a wide range of products such as toothpastes and mouthwashes. Several studies demonstrated the efficiency of such therapeutic substances against gram-positive microorganisms, (e.g., Streptococcus mutans [ 10 , 11 ], Staphylococcus aureus [ 12 ], Lactobacillus spp. [ 13 ], and Actinomyces spp.…”
Section: Introductionmentioning
confidence: 99%